Improving the Quality of Digital-Based Education for Students of SMK Cendikia Rancakalong Sumedang - Rajiv Dharma Mangruwa; Moh Faidol Juddi; A Hasan Al Husain (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Massive innovations have always influenced human civilization. Technological development is considered one of them. Today, we can see the massive creation of human ideas and the increasing development of technology that can support daily human activities more efficiently and effectively. The presence of technology in education requires students to be able to speak in virtual public spaces, both to meet the demands of school assignments and interact with other people. It required students to improve the quality of education technology based. Therefore, the presence of the Telkom University lecturer team aims to provide digital literacy in the digital world, theory, and practice, to students at SMK Cendekia. The ability to have digital knowledge is needed by students, especially vocational students, who later, after graduating from school, might have to go directly to the world of work. Some take part in the selection to enter college. The ability of education digital bases will help students control the unique combination of skills, experience, and personality in the world to see outside of the standard practices. It creates an opportunity to follow the trends of worldwide practices. Supporting school children's personal branding is important to become a superior generation. The results of the implementation of this activity include (1) personal branding, (2) Public speaking, and (3) Motivation.